Unique cardiac magnetic resonance imaging findings of progressing myocardial damage in a patient with polymyositis - Noboru KITAMURA; Hitomi KOBAYASHI; Masami TAKEI; Yasuyuki KOBAYASHI (Archives of Rheumatology, 2021)
A 42-year-old female patient admitted to our hospital with muscular weakness and palpitations. Skeletal muscle biopsy reveled infiltration of lymphocytes surrounding muscle fibers consistent with the diagnosis of polymyositis (PM). Conventional cardiac angiography showed absence of macrovascular stenosis. The histopathological finding of myocardial biopsy was consistent with acute myocarditis. We performed cardiac magnetic resonance imaging (CMRI) to evaluate myocardial damage. Images were assessed for late gadolinium enhancement (LGE), T2-weighted imaging (T2WI) and extracellular volume (ECV) fraction. LGE images showed patchy enhancement in the septum and curvilinear myocardial enhancement in the inferolateral wall (Figure 1a). CMRI one year later revealed not significantly changed LGE (Figure 1b), expansion three years later (Figure 1c) and more expansion five years later (Figure 1d) without creatinine kinase elevation and cardiac symptoms. After five years, no significant abnormalities were seen in T2WI (Figure 2a). ECV fraction increased in the myocardial layer of anterolateral wall, the middle layer of septum and the papillary muscle, consistent with the region of LGE (Figure 2b, c). ECV can detect diffuse myocardial edema in areas that do not exhibit abnormalities on T2WI. Presumably, this is active inflammatory cell infiltration. Myocarditis in PM with such a unique LGE pattern is rare. There are a few reports of ECV increasing heterogeneously in PM. Cardiac involvement in PM is a frequent complication and often life-threatening.[1,2] Despite alleviating inflammation and dissipation of symptoms, asymptomatic myocardial damage progressed gradually in this case. CMRI including ECV can be a useful method of evaluating myocardial damage. <f1><f2>